2015
DOI: 10.1111/bph.13026
|View full text |Cite
|
Sign up to set email alerts
|

Δ9Tetrahydrocannabinol attenuates Staphylococcal enterotoxin B‐induced inflammatory lung injury and prevents mortality in mice by modulation of miR‐17‐92 cluster and induction of T‐regulatory cells

Abstract: BACKGROUND AND PURPOSEStaphylococcal enterotoxin B (SEB) is a potent activator of Vβ8+T-cells resulting in the clonal expansion of ∼30% of the T-cell pool. Consequently, this leads to the release of inflammatory cytokines, toxic shock, and eventually death. In the current study, we investigated if Δ 9 tetrahydrocannabinol (THC), a cannabinoid known for its anti-inflammatory properties, could prevent SEB-induced mortality and alleviate symptoms of toxic shock. EXPERIMENTAL APPROACHWe investigated the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 75 publications
5
72
0
Order By: Relevance
“…To identify other genes whose expression might be regulated by THC, we used RNA-seq to compare the abundance in SEB-activated LN cells or CD4 ϩ T cells, with and without THC treatment. Some genes such as Il-4 identified in this study have already been shown in our previous studies and those of others (7,21). Interestingly, many genes such as Fpr2, which has been shown to have an anti-inflammatory role (26), but has never been shown previously to be induced by THC were also identified.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…To identify other genes whose expression might be regulated by THC, we used RNA-seq to compare the abundance in SEB-activated LN cells or CD4 ϩ T cells, with and without THC treatment. Some genes such as Il-4 identified in this study have already been shown in our previous studies and those of others (7,21). Interestingly, many genes such as Fpr2, which has been shown to have an anti-inflammatory role (26), but has never been shown previously to be induced by THC were also identified.…”
Section: Discussionsupporting
confidence: 79%
“…Suppression of miR-17/92 cluster by THC has been shown in another animal model (21). Indeed, the expression of precursor of this miRNA cluster was downregulated by THC in this study.…”
Section: Mirna Precursors With Altered Expression After Thcsupporting
confidence: 75%
See 3 more Smart Citations